Authorship of a short story attributed to Jorge Miota - Wise, David O. (2020)
The short story La pared de enfrente appeared in the Lima magazine Actualidades Revista Ilustrada in 1903. The authorship of the text has repeatedly been attributed to Jorge Miota, a minor Peruvian literary figure of the early 20th century. The attribution is incorrect. La pared de enfrente is in fact Miota’s translation of the story Le mur d’en face by the internationally known French author Pierre Loti. Both Loti’s story and Miota’s translation show fine craftsmanship.